010 Prevention of shoulder and elbow injuries in high school baseball players: a time-to-event analysis. (3rd March 2020) - Shitara, Hitoshi; Tajika, Tsuyoshi; Hamano, Noritaka; Sasaki, Tsuyoshi; Kamiyama, Masataka; Fukui, Kurumi; Chikuda, Hirotaka
Abstract : Background: Decreased range of motion (ROM) and muscle weakness in the dominant shoulder are known as significant risk factors for shoulder and elbow injuries in high school baseball pitchers. However, there is no previous study investigating the outcomes of upper-body injury prevention programs for these risk factors. Objective: We prospectively investigate if a prevention program to improve the risk factors reduces the incidences of shoulder and elbow injuries. Design: Interventional study. Setting: High school league. Participants: Ninety-two male high school baseball pitchers participated. Exclusion criteria: (1) prior injury to the throwing arm, (2) unable to throw, or (3) performed daily muscle-specific rotator cuff training or posterior capsule/sleeper stretches. Interventions: Participants were taught to perform stretching and strength exercises aimed at improving shoulder internal rotation ROM and external rotation strength in the preseason. The pitchers freely chose to participate in one of four groups [SM-group: performed both exercises, S-group: performed stretching exercise only, M-group: performed strength training alone, and N-group: performed neither intervention]. Injury was defined as inability to play for ≧8 days because of shoulder/elbow symptoms. Main outcome measurements: For a time-to-event analysisthe Kaplan-Meier survival curves were generated and hazard ratios (HRs) for injury occurrence were calculated using multivariate Cox regression. Log-rank tests were used for between-group comparisons of survival distributions. Results: Injuries occurred in 25%, 35% and 57% of participants and median times to injury were 89, 92, and 29.5 days in the S (n=32), SM (n=46) and N (n=14) groups, respectively. Nobody chose the M group. HRs were 0.36 and 0.47 for the S and SM group, respectively, based on the N group as reference. The incidence of injury was significantly lower in the S group than in the N group ( p =0.04). Conclusions: Shoulder stretching significantly prevented baseball-related shoulder and elbow injures and significantly prolonged pitching availability during the season.